Development of canned dalanghita (Citrus Nobilis Lour. Var. Szinkom) juice with Sacs - Jutba, Ruth Libertine B.
The study was undertaken to develop a ready-to-drink canned dalanghita juice with sacs. Along with developing the descriptive scoresheet, the product profile was established. 14°Bx - 0.4667 % titratable acidity was found to be the most acceptable blend based on sensory evaluation. In terms of off-flavor, there was no significant difference between the blanched an unblanched samples. However, unblanched samples were generally more acceptable. The adequate thermal process for canned dalanghita juice with sacs was determined through the heat penetration study. Microbiological analysis, physico-chemical test and sensory evaluation were conducted to test the adequacy of the process. The appropriate thermal process schedule was found to be at 212°F for 4 minutes. This process was verified on a larger scale.